THE POTENTIAL OF FRANGIPANI FLOWER EXTRACT (Plumeria alba L.) AS AN ANTIBACTERIAL - Sinaga, Hana Yuniestica; Jaya, Made Krisna Adi (Journal Pharmaceutical Science and Application; Vol 4 No 1 (2022): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2022.v04.i01.p05, 2022)
Background: Bacteria develop naturally in the human body to aid in protecting the individual. Antibiotic resistance is quickly increasing and is becoming a global health concern. In this situation, the risk of synthetic antibiotic resistance against bacterial infections makes it critical to find alternative medications that are safe, easy to obtain, and better than synthetic antibiotic alternatives. The frangipani plant is one of the medicinal plants used in traditional medicine as an antibacterial. The frangipani plant possesses antibacterial properties comparable to broad-spectrum medicines against uro-gastro pathogens. Objective: The purpose of this study was to determine the activity of the frangipani flower as an antibacterial. Methods: studying literature from various databases, websites, national journals, and relevant international journals to identify frangipani flowers with antibacterial activity. Results: Results showed that frangipani flowers have antibacterial activity against gram-positive and gram-negative bacteria because frangipani flowers contain various antibacterial chemical components, such as terpenoids, saponins, phenols, flavonoids, tannins, and essential oils. Conclusion: Frangipani flowers have the potential to an antibacterial against gram-positive and gram-negative bacteria. Keywords:  Frangipani flower, Antibacterial, Bacteria